Supreme decisions : great constitutional cases and their impact - Urofsky, Melvin (Westview Press, 2012)
Compellingly written, accessible, and interpretive, Melvin I. Urofsky's stories of major Supreme Court cases and the impact of each ruling on American constitutional law make a readable book for every student.